The Contribution of Islamic Micro Finance Towards Poverty Alleviation: A Case Study of Bank of Khyber Khud Kifalat Scheme - Muhammad Saleem Qazi; Dr. Muhammad Adil; Dr. Saima Batool; Yasir Khan (Journal of Business & Tourism, 2021)
The aim of this research is to investigate role of Microfinance in Poverty alleviation. Primary data was used in this research and was collected through personally administered questionnaires from 150 respondents. Results showed that most of the respondents were in favor of the Khud Kafalat scheme because it helped them in increasing their living standards and standard of education of their children due to establishing small scale businesses or expanding existing businesses. Moreover, Khud Kafalat Scheme has a very important role in Poverty alleviation and increased their gross monthly income. Furthermore, their satisfaction can also be depicted from the fact that although they observed no change in their employees’ condition but on individual level, most of them, were still in favor of applying again for the loan, if needed, in the future.